An expedient approach to 1, 2-dihydroisoquinoline derivatives via cobalt catalysed 6-endo dig cyclization followed by Mannich condensation of o-alkynylarylaldimines. Issue 4 (1st December 2014) - Urvashi; Rastogi, Gaurav K.; Ginotra, Sandeep K.; Agarwal, Alka; Tandon, Vibha
Abstract : A highly effective 6- endo dig cyclisation of o -alkynyl aldimines to 1, 2-dihydroisoquinolines has been described via direct and nitro Mannich condensation using inexpensive and readily available cobalt chloride as catalyst. Abstract : A highly effective 6- endo dig cyclisation of o -alkynylaldimines to 1, 2-dihydroisoquinolines has been described via direct and nitro Mannich condensation using inexpensive and readily available cobalt chloride as catalyst. This strategy provides an effective procedure for the synthesis of substituted 1, 2-dihydroisoquinolines derivatives in moderate to high yields. An addition of pronucleophiles, such as nitromethane, acetone and α-hydroxyacetone, to o -alkynylarylaldimines has been achieved via isoquinolinium intermediate.